How do you solve #3x+6y=-6# and #-7x+y=29# using substitution?

1 Answer
Apr 1, 2018

Answer:

#(x,y)=(-4,1)#

Explanation:

Solve one of these equations for #y# to make substitution possible. The second equation appears best suited for this:

#-7x+y=29#

#y=7x+29#

We can now replace all instances of #y# in the first equation with #7x+29:#

#3x+6(7x+29)=-6#

#3x+42x+174=-6#

#45x=-6-174#

#45x=-180#

#x=-180/45#

#x=-4#

To find #y,# plug in the result above into either of the two equations. We solved the second one for #y,# so that will be the easiest one to use:

#y=7(-4)+29#

#y=1#